Credit default swaps, exacting creditors and corporate liquidity management - Subrahmanyam, Marti G.; Tang, Dragon Yongjun; Wang, Sarah Qian (Journal of Financial Economics, 2017)
We investigate the liquidity management of firms following the inception of credit default swaps (CDS) markets on their debt, which allow hedging and speculative trading on credit risk to be carried out by creditors and other parties. We find that reference firms hold more cash after CDS trading commences on their debt. The increase in cash holdings is more pronounced for CDS firms that do not pay dividends and have a higher marginal value of liquidity. For CDS firms with higher cash flow volatility, these increased cash holdings do not entail higher leverage. Overall, our findings are consistent with the view that CDS-referenced firms adopt more conservative liquidity policies to avoid negotiations with more exacting creditors.